EFFECT TETRAHYDROCURCUMIN AND PTEROSTILBENE ON LIPID PEROXIDATION AND LIPIDS IN STREPTOZOTOCIN - NICOTINAMIDE INDUCED DIABETIC RATS - Pidaran Murugan, (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Pterocarpus marsupium has been used in the treatment of toothache, diarrhoea, heartburn, urinary tract infections, boils, sores and skin diseases. P. marsupium has been used for many years in the treatment of diabetes mellitus. Pterostilbene was found to be one of the active constituents in the extracts of the heartwood of Pterocarpus marsupium. Pterostilbene, a phenolic compound derived from resveratrol, possesses greater bioavailability than its parent compound due to the presence of two methoxyl groups. In this review, the beneficial effects of pterostilbene on diabetes, liver steatosis and dyslipidemia are summarized. Pterostilbene is a useful bioactive compound in preventing type 1 diabetes, insulin resistance and type 2 diabetes in animal models. Hyperlipidemia is an associated complication of diabetes mellitus. We recently reported that Tetrahydrocurcumin (THC) and pterostilbene lowered the blood glucose in diabetic rats. THC 80mg/kg body weight and Pterostilbene 40 mg/kg body weight was orally administered to diabetic rats for 45 days, resulted a significant reduction in blood glucose and significant increase in plasma insulin in diabetic rats, which proved its antidiabetic effect. THC and pterostilbene also caused a significant reduction in lipid peroxidation (thiobarbituric acid reactive substances and hydroperoxides) and lipids (cholesterol, triglycerides, free fatty acids and phospholipids) in serum and tissues, suggesting its role in protection against lipid peroxidation and its antihyperlipidemic effect. THC showed a better effect when compared with pterostilbene.